PERTANGGUNG JAWABAN PIDANA DALAM TINDAK PIDANA PERJUDIAN(KAJIAN ATAS PUTUSAN NO. 1931 K/Pid/2009) - Alex Irianto; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the middle of combating gambling spirit proclaimed by the government of therepublic Indonesia, does not correspond to the facts on the ground. The rise ofgambling that occurs at all levels of society has reached to the point that it ischaracterized by an alarming number of cases of gambling were dismantled bythe police. Although it has no legal basis to regulate it but the offense persists.High profits can be obtained by the perpetrators of gambling so many people areattracted to the game. In this case gambling is often associated with poverty in thecommunity or custom factors existing in society. So many people who come fromthe middle and lower class participate in gambling because of the lure of profitthat can be obtained is very high if you win. In this case the Cindra Wijaya aliasAcin, known as the king of gambling pekanbaru experiencing lengthy judicialprocess so that it becomes a case that became a media focus.This research included into the normative legal research is research thatexamines the legal norms rooted in the rule of law is a law. This research wasconducted by examining the library materials or secondary formulated normativeresearch or research library book. In terms of nature of this research isdescription research that aim to describe or depict clearly and in detail. ,From the research, there are two main things that can be inferred. First, the judgein the consideration convict the defendant Chindra Wijaya, more focused on thethings or aggravating circumstance the defendant rather than things oraggravating circumstances and sentenced the defendant for 4 (four) years andseizure of evidence. Second, the basic consideration in the judge's decision toexamine and decide Case Number accordance with the principles of justice whichis the maximum punishment for the perpetrators because proven legally andconvincingly guilty of the crime of participation in gambling.Keywords: Gambling, Acin, King Gambling From Pekanbaru